Preparation and Sintering Effect in Quartz-Barium Titanate Porous Ceramics and Permeability Modulation Using an Implanted Electrode - Ernesto Suaste Gómez; José de Jesús Agustín Flores Cuautle; Omar Terán Jiménez (Advances in Materials Science and Engineering)
Barium titanate and quartz mixed in different proportions were used to create porous piezoelectric ceramics. Three different sintering temperatures were used for the ceramics preparation; a nichrome wire was used as internal electrode in porous ceramics. Characteristics as porous area, porosity, and its relationship with quartz percentage and sintering temperatures were studied. Porous ceramics with an implanted electrode were created, by applying an alternating voltage in the internal electrode that controlled the liquid permeability coefficient, calculated by the Darcy Law.